An investigation of the international student mathematics learning environment: Aligning pedagogy to the language needs of foundation students - Churchill, Pat (Curtin University, 2014)
Teaching International students mathematics and statistics immediately places the focus on the use of language. This study will investigate ways in which mathematical or mathematics specific language is important in mathematics. It will identify key enablers or inhibitors of effective mathematics education that may be linked to mathematics language. This study will look at how language can enhance conceptual understanding in mathematics and the teaching pedagogy that supports this. Gender differences will also be identified.